2015
DOI: 10.1037/pas0000127
|View full text |Cite
|
Sign up to set email alerts
|

Interpretation of KABC-II scores: An evaluation of the incremental validity of Cattell-Horn-Carroll (CHC) factor scores in predicting achievement.

Abstract: This study is an examination of the incremental validity of Cattell-Horn-Carroll (CHC) factor scores from the Kaufman Assessment Battery for Children-second edition (KABC-II) for predicting scores on the Kaufman Test of Educational Achievement-second edition (KTEA-II). The participants were children and adolescents, ages 7-18, (N = 2,025) drawn from the KABC-II standardization sample. The sample was nationally stratified and proportional to U.S. census estimates for sex, ethnicity, geographic region, and paren… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 50 publications
(59 reference statements)
1
5
1
Order By: Relevance
“…These results are similar to previous findings (McGill, ) with the alternative CHC interpretive model. However, direct comparison with the incremental validity results from McGill () showed that in the present study, the combined KABC‐II Luria factor scores provided less incremental prediction of the KTEA‐II Reading Comprehension score at ages 13 to 18 years (2%) and the Oral Language Composite across the school‐age span (1%–3%). In contrast, increased prediction was observed for Written Expression at ages 13 to 18 years.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…These results are similar to previous findings (McGill, ) with the alternative CHC interpretive model. However, direct comparison with the incremental validity results from McGill () showed that in the present study, the combined KABC‐II Luria factor scores provided less incremental prediction of the KTEA‐II Reading Comprehension score at ages 13 to 18 years (2%) and the Oral Language Composite across the school‐age span (1%–3%). In contrast, increased prediction was observed for Written Expression at ages 13 to 18 years.…”
Section: Discussionsupporting
confidence: 93%
“…With respect to the KABC‐II, McGill () utilized similar procedures to assess the incremental predictive validity of the CHC model scores and found that whereas the Fluid‐Crystallized Index (FCI) accounted for clinically significant portions of criterion achievement variance, the CHC factor scores accounted for trivial portions of achievement after controlling for the effects of the FCI. Again, these results are not useful for making inferences about the clinical utility of Luria model scores because the measurement model for that interpretive scheme differs from the CHC model.…”
Section: Incremental Predictive Validitymentioning
confidence: 99%
“…Whereas, related predictive validity studies with cognitive measures (e.g., Benson, Kranzler, & Floyd, 2016;Canivez, 2013a;McGill, 2015aMcGill, , 2015bMcGill & Spurgin, 2016) have largely suggested that broad and narrow cognitive abilities account for trivial portions of achievement after controlling for general ability, the present results suggest that this conclusion as a general rule may be overstated. As previously mentioned, although the GIA consistently accounted for large reading effects, lower-order scores accounted for meaningful incremental prediction in several circumstances.…”
Section: Discussioncontrasting
confidence: 51%
“…Incremental validity studies using HMRA have been conducted previously on the WJ III COG (McGill, 2015a;McGill & Busse, 2015) and other related intelligence tests (e.g., Canivez, 2013a;McGill, 2015b;McGill & Spurgin, 2016). Across these studies, it was consistently demonstrated that the omnibus full scale IQ score accounted for most of the reliable achievement variance that could be predicted in the regression models and that little additional incremental variance was accounted for by the lower-order broad and narrow ability scores after controlling for the predictive effects of the general factor.…”
Section: Introductionmentioning
confidence: 92%
“…For instance, previous evaluations of earlier additions of the WIAT have noted minimal effects for cognitive index scores above and beyond strong effects from the FSIQ on achievement (Glutting et al, 2006). These findings hold true for the WJ-III (McGill, 2015a; McGill & Busse, 2015) and the KABC-2 (McGill, 2015b). The inclusion of the FSIQ, such as from the Wechsler Intelligence Scale for Children–Fifth Edition (WISC-V; Wechsler, 2014) may affect these results in a similar manner.…”
Section: Discussionmentioning
confidence: 52%